Evropski parlament na razpotju - Koritnik, Boštjan (Pravnik, 2023)
In the spring of 2024, the European Parliament gears up for its tenth direct election since 1979, marking another crucial milestone in transnational democracy following the Conference on the Future of Europe. Historically, EP elections have been marred by national fragmentation and perceived as “second-class” due to low voter turnout in many Member States, including Slovenia. Nonetheless, these elections are still a central act for ensuring the democratic legitimacy of the EU and shaping its political trajectory. This article is a report from the event, the topic of which were the current challenges of European parliamentary democracy, especially one year before the European elections, such as the renewal of EU electoral rules, the promotion of electoral participation, and the proposition for an independent EU ethics authority.
Keywords: etika; Evropska unija; Evropski parlament; mladina; ocene in poročila; parlamentarna demokracija; prihodnost; volitve